Airplane flying handbook (Skyhorse Publishing, 2017)
The Federal Aviation Administrations Airplane Flying Handbook provides pilots, student pilots, aviation instructors, and aviation specialists with information on every topic needed to qualify for and excel in the field of aviation. Topics covered include: Ground operations Cockpit management The four fundamentals of flying Integrated flight control Slow flights Stalls Spins Takeoff Ground reference maneuvers Night operations And much more Updated to include the most current information, the Airplane Flying Handbook is a great study guide for current pilots and for potential pilots who are interested in applying for their first license. It is also the perfect gift for any aircraft or aeronautical buff.